Herdsmen and Farmers Conflict in Tivland 2000-2024: A Resource Dimension - Mnda , Terver; Tyonongo, Matthew Terwase (Kashere Journal of Politics and International Relations, 2025)
Herdsmen and farmers clashes have become a recurring decimal in Tivland in recent times. This resource-use conflict has permeated the socio-economic milieu of Tivland in all facets of its existence. The methodology used for this work is content analysis. The paper has also used the political economy theory in general and the frustration-aggression theory in particular as its frameworks of analysis. Upon critical analysis, the paper has shown that this resource conflict has negatively affected agricultural activities in Tivland. It has also led to destruction of farmlands and even harvested crops leading to loss of revenue, hunger, malnutrition and general impoverishment. The paper has therefore suggested inter alia that there should be ranching of cattle, military operations should be strengthened and there should be a cultural reorientation to educate different ethnic groups about the culture and tradition of other ethnic groups.